2018
DOI: 10.1186/s12885-017-3960-7
|View full text |Cite
|
Sign up to set email alerts
|

MGAT1 is a novel transcriptional target of Wnt/β-catenin signaling pathway

Abstract: BackgroundThe Wnt/β-catenin signaling pathway is an evolutionary conserved pathway, which has important functions in vertebrate early development, axis formation, cellular proliferation and morphogenesis. Additionally, Wnt/β-catenin signaling pathway is one of the most important intracellular pathways that controls cancer progression. To date most of the identified targets of this pathway are shown to harbor tumorigenic properties. We previously showed that Mannosyl glycoprotein acetylglucosaminyl-transferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…At the same time, all proteins could be up‐regulated by exogenous bFGF added into DMEM‐LG. Furthermore, those proteins could also be up‐regulated by LiCl (20 mmol/L) added into DMEM‐LG, which is a widely used in the activation of Wnt/β‐catenin signalling . However, those proteins were again down‐regulated in iPS‐CM by XAV939 (XAV, 10 μmol/L) (Figure D,E), an inhibitor of the Wnt/β‐catenin signalling pathway .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, all proteins could be up‐regulated by exogenous bFGF added into DMEM‐LG. Furthermore, those proteins could also be up‐regulated by LiCl (20 mmol/L) added into DMEM‐LG, which is a widely used in the activation of Wnt/β‐catenin signalling . However, those proteins were again down‐regulated in iPS‐CM by XAV939 (XAV, 10 μmol/L) (Figure D,E), an inhibitor of the Wnt/β‐catenin signalling pathway .…”
Section: Resultsmentioning
confidence: 99%
“…22 The results of Western blotting analysis showed that the levels of b-catenin and its target proteins cyclin D1, c-Myc and survivin in iPS-CM group were higher than those in Furthermore, those proteins could also be up-regulated by LiCl (20 mmol/L) added into DMEM-LG, which is a widely used in the activation of Wnt/b-catenin signalling. 39,40 However, those proteins were again down-regulated in iPS-CM by XAV939 (XAV, 10 lmol/L) ( Figure 6D,E), an inhibitor of the Wnt/b-catenin signalling pathway. 41 These results indicated that iPS-CM might be mainly relied on inherent bFGF to promote the proliferation of ILCs through Wnt/ b-catenin signalling pathway.…”
Section: Effects Of Ips-cm On Medium Testosterone (T) Levels and Stmentioning
confidence: 98%
“…β-catenin is defined as an oncogene as well as a critical part in the Wnt pathway [40]. It plays an essential role in regulating cancer cell progression, early vertebrate development, and axis formation [41]. HMGB2 was found to be involved in the activation of the Wnt/β-catenin signaling pathway during GC development.…”
Section: Discussionmentioning
confidence: 99%
“…Stable overexpression of the MGAT1 gene in the Huh7 cell line resulted in a significant increase in tumor growth rate in severe combined immunodeficiency (SCID) mice. Down-regulation of MGAT1 expression in the liver can significantly reduce hepatic steatosis in mice, while reducing body weight and increasing glucose tolerance (Lee et al, 2012;Akiva and Birgul Iyison, 2018).…”
Section: Discussionmentioning
confidence: 99%